Crônica mexicana de Hernando Alvarado Tezozómoc e as redes de inteligibilidade da memória (1538-1598) - Fukunaga, João Luiz (2008)
This dissertation begins with an attempt to investigate Hernando Alvardo Tezozómoc. Nevertheless, the problems arising from the document comprise a board temporal gap, as it s only when his masterpiece, the Cronica Mexicana is written, in 1598, that we first note the existence of such a in-between-spaces subject as the author was, whereas it s between the years of 1521 and 1598 that we may first find the social-political and cultural foundations for this historical subject. Therefore, this project intends to analyze this 16th century chronicle in search of Tezozómoc, a member of the mexica and colonial society elite, the latter a result of several contact relationships. In this work, I intend to seek the understanding of how this historical speech was born inside a specific social group in the colonial society as well as how it became a tool to legitimate said group when facing the social, political and economical pressures that shook the privileged position and status they had previously acquired